Simulation Model of Servo Motor by Using Matlab - Fatin Nabeel Abdullah; Ghada Adel Aziz; Salam Waley Shneen (Journal of Robotics and Control (JRC), 2022)
The research aims to develop documented empirical data to obtain a high-accuracy and effective system according to a principal system as a model that represents the system for all expected cases and different working conditions. The current works are simulating a servo motor that works with specifications as a mathematical representation of it down to its representation with a transformation function. The simulation is done for different cases, the first is without a controller, and the other is an operation simulation with a conventional controller that is with a PID controller. The results, through response and accuracy, prove the preference of PID controller systems in the speed of response and high accuracy with the change or different conditions of the system, i.e., working with linear systems. A simulation is being conducted to verify the use of control systems to improve the performance of servo motors. Algorithms of control systems are developed according to designs based on prior experience. Speed and position control are the most common and used in many applications, which created the need to choose them. To overcome fluctuations and obtain a quick response and a high-precision system used, control systems, as the results proved. The research contribution is developing a design for the user control systems also checking them in simulation with the servo motor system using MATLAB. They test them in the servo motor control as well to test their performance experimentally.